Kebangkitan Manusia di Akhirat Menurut Al-Ghazali Dan Ibnu Rusyd - Ruyatul Fauziah (Aqlania: Jurnal Filsafat dan Teologi Islam, 2018)
The dogma of resurrection after death is a very interesting subject to discuses since it contains controversy among Moslem schoolers. It hase being by philosophers since medieval era. Al-Ghazali outlined rejection against the philosophers about bodily resurrection in his book entitled Tahafut al-Falasifah (Confusions of the Philosophers), precisely in the last issue of the twenty issuesdiscussing the absence of a physical generation. Responding to the attack, Ibnu Rushd appeared to defend the philosophers of the attack and pagan. It is in this context Ibnu Rushd wrote is book Tahafut al-Tahafut (The Ambiguity of the Book Ambiguity).Departing from this background the author proposes research questions as follows : 1). How the thought of Al-Ghazali and Ibnu Rushd about human resurrection in the afterlife. 2). What are the causes and implications of about Al-Ghazali, as and Ibnu Rushd different talk about human resurrection in the afterlife. Goals to a achiev from the study are : 1). to comprehend the thought ofAl-Ghazali and Ibn Rushd about human resurrection in the afterlife. 2). to determine the causes and implications of Al-Ghazali and Ibnu Rushd thoughts on the respective issue.In terms of methodology, the author follows several steps : Determinain data sources, collecting data, and arrange data, and analyzing data. Primary data is retrieved from Al-Ghazali’s book Tahafut al-Falasifah especially on the twenty issues and that of Ibnu Rushd Tahafut al-Tahafut. Secondary data is retrieved from books related to Al-Ghazali and Ibnu Rusyd. The collected datais analyzed by comparative method.Conclusions of this study are as follow: First, Al-Ghazali holds that the surrection will occur in body and soul. On the other hand, Ibnu Rushd and other philosophers maintain that the revival will occur only in soul. Secondly, the cause of this disagreement is the difference in interpreting the Qur’anic verses of resurrection. As for Ibnu Rushd, philosophers’ exegesis does not mean toreduce sense of primacy of the hearafter. Therefore, this implies that the philosophers should not be the subject of infidel accuse just because of their thoughts. Nevertheless, their exegesis to the verses should not be exposed publicly to general.